Tar, nicotine, and carbon monoxide yields of some Nigerian cigarettes. - Awotedu, A A (1983)
Fourteen cigarette brands manufactured in Nigeria in 1981 were analysed to determine the tar, nicotine, and carbon monoxide yields. Five of the brands belonged to the high and middle to high tar category (greater than 22 mg/cigarette) and nine to the middle tar (17-22 mg/cigarette) category. None of the cigarettes was in the low to middle and low tar (less than 17 mg/cigarette) category. The nicotine and carbon monoxide yields were similar to those of European cigarettes. Tobacco companies need to manufacture low tar cigarettes in the Third World as is the practice in the economically developed parts of the world.